Polarization-Maintaining Single-Frequency Fiber Laser With Quadruple Wavelengths at the C-Band - Kunyi Li; Huaqiu Deng; Pengfei Ma; Wei Lin; Huihui Cheng; Xianchao Guan; Changsheng Yang; Qilai Zhao; Yuning Zhang; Zhongmin Yang; Shanhui Xu (IEEE Photonics Journal, 2018)
In this paper, a polarization-maintaining quad-wavelength (QW) single-frequency fiber laser (SFFL) at the C-band with the novel and compact structure is demonstrated. Applying the rate equations and multiple coupled nonlinear Schrödinger equations, the theoretical model of QW fiber lasers is established, and then the optical spectra, temporal evolution, and stability of the QW fiber laser are analyzed numerically. Based on the theoretical analysis, a QW-SFFL having an ultrashort linear distributed Bragg reflector cavity is proposed. Utilizing a wideband fiber Bragg grating coupled with a dual-channel polarization maintaining fiber Bragg grating as the wavelength selection and a 15-mm-long Er3+/Yb3+ co-doped phosphate fiber as the gain medium has realized a robust QW laser with the wavelength spacing of 0.4 nm. All the wavelengths maintain the single-frequency operation independently with the linewidths of 20 kHz. This type of compact SFFLs with quadruple wavelengths is widely adapted to lidar systems and fiber sensing.